Local and Systemic Effects of Intra-arterial Desmopressin in Healthy Volunteers and Patients with Type 3 von Willebrand Disease - Newby, David E.; Stewart, Andrew; Witherow, Fraser N.; Grieve, Susan; Dawson, Pamela; Fox, Keith A. A.; Webb, David J.; Ludlam, Christopher A. (Thrombosis and Haemostasis, 2000)
Intra-arterial desmopressin caused dose and time dependent increases (p <0.001 for all) in forearm blood flow (all doses) and plasma tissue plasminogen activator (t-PA) concentrations (desmopressin ≥70 ng/min). Although plasma t-PA concentrations rose in both forearms, there was a modest local release of t-PA in the infused forearm (14 ng/100 mL of tissue/min, p <0.05). At desmopressin doses ≥300 ng/min, plasma von Willebrand factor (vWf) and Factor VIII:C concentrations rose in both forearms (p <0.001) and correlated with the rise in interleukin-6 concentrations (r = 0.92, p <0.001; r = 0.85, p = 0.002 respectively). Neither desmopressin nor substance P caused t-PA, vWf or Factor VIII:C release in the patients, although desmopressin increased plasma interleukin-6 concentrations as in healthy volunteers. We conclude that desmopressin releases t-PA, vWf and Factor VIII:C predominantly via systemic mechanisms, possibly mediated by cytokine release. Patients with type 3 vWD appear to have a generalised failure to release t-PA acutely despite a normal interleukin-6 response to desmopressin infusion.
Keywords: Plasminogen activators; desmopressin; von Willebrand factor; interleukin-6; factor VIII:C